Cabo Verde : First Review Under the Policy Coordination Instrument and Request for Modification of Targets. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper highlights Cabo Verde's First Review Under the Policy Coordination Instrument (PCI) and Request for Modification of Targets. Performance under the PCI-supported program has been strong. All reform targets were met, with some measures put in place ahead of schedule; and all end-September 2019 quantitative targets were met, except for the floor on tax revenue, missed by a narrow margin due to lower-than-projected taxes on international trade. Economic prospects for 2020 are clouded by the expected impact of coronavirus disease 2019 (COVID-19), resulting from the global economic downturn and travel restrictions which adversely affect tourism flows, foreign direct investment and remittances. Coordinated support from Cabo Verde's development partners will be needed to support the authorities' efforts in addressing the economic and social impact of COVID-19. The medium-term outlook remains positive although risks are tilted to the downside. Growth is expected to rebound in 2021 and return to the pre-COVID-19 medium-term trajectory of about 5 percent as the global economy recovers, and the authorities maintain their structural reform efforts to improve the business environment and build the economy's resilience to adverse shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet